Influence of dual‐specificity protein phosphatase 5 on mechanical properties of rat cerebral and renal arterioles - Huawei Zhang; Chao Zhang; Yedan Liu; Wenjun Gao; Shaoxun Wang; Xing Fang; Ya Guo; Man Li; Ruen Liu; Richard J. Roman; Peng Sun; Fan Fan (Physiological Reports, 2020)
Abstract We recently reported that KO of Dual‐specificity protein phosphatase 5 (Dusp5) enhances myogenic reactivity and blood flow autoregulation in the cerebral and renal circulations in association with increased levels of pPKC and pERK1/2 in the cerebral and renal arteries and arterioles. In the kidney, hypertension‐related renal damage was significantly attenuated in Dusp5 KO rats. Elevations in pPKC and pERK1/2 promote calcium influx in VSMC and facilitate vasoconstriction. However, whether DUSP5 plays a role in altering the passive mechanical properties of cerebral and renal arterioles has never been investigated. In this study, we found that KO of Dusp5 did not alter body weights, kidney and brain weights, plasma glucose, and HbA1C levels. The expression of pERK is higher in the nucleus of primary VSMC isolated from Dusp5 KO rats. Dusp5 KO rats exhibited eutrophic vascular hypotrophy with smaller intracerebral parenchymal arterioles and renal interlobular arterioles without changing the wall‐to‐lumen ratios. These arterioles from Dusp5 KO rats displayed higher myogenic tones, better distensibility, greater compliance, and less stiffness compared with arterioles from WT control rats. VSMC of Dusp5 KO rats exhibited a stronger contractile capability. These results demonstrate, for the first time, that DUSP5 contributes to the regulation of the passive mechanical properties of cerebral and renal arterioles and provide new insights into the role of DUSP5 in vascular function, cancer, stroke, and other cardiovascular diseases.